Answer:
what is the question?
Step-by-step explanation:
Answer: Option A -439
(s o t)(x)=s(t(x))
(s o t)(-7)=s(t(-7))
x=-7→t(-7)=3(-7)→t(-7)=-21
(s o t)(-7)=s(t(-7))=s(-21)
x=-21→s(-21)=2-(-21)^2=2-441→s(-21)=-439
(s o t)(-7)=s(t(-7))=s(-21)=-439
Answer: Option A -439
Answer:
5x+5,3x-6y
Step-by-step explanation:
<span><span>To find the area of a rectangle, multiply the length by the width. The formula is:</span><span>, where is the area, is the length, is the width, and · means multiply.</span><span>A square is a rectangle with 4 equal sides. To find the area of a square, multiply the length of one side by itself. The formula is:</span><span> or , where A is the area, s is the length of a side, and · means multiply.</span></span>
$11 an hour, because 82.5/7.5=11